Importance of Night Dreams in Ibsen's Plays A Psychoanalytic study of The Vikings of Helgeland and Little Eyolf - Bardzimashvili, Nino (2014)
The topic for my thesis is the importance of night dreams in Henrik Ibsen's plays. My study of the subject is based on two plays, The Vikings of Helgeland and Little Eyolf. The first one is a historical play written in 1857 and is usually discussed in relationship with nationalism and the political events in 19th century Norway. The second one is known as a "family romance" and was written in 1894. These two plays represent different periods of Henrik Ibsen's writing and hence it is possible to observe the changing author's viewpoint on various subjects; however both texts contain night dreams. In my thesis I have presented a psychoanalytical analysis of The Vikings of Helgeland and of Little Eyolf. In order to give a comprehensive picture of the importance of dreams in Ibsen's works I have focused not only on night dreams out of context with the rest of the text but on a number of aspects that are connected to the these plays such as historical, biographical, cultural, political, social and moral. To prepare a solid basis for my research I have studied articles and books related to the subject, explored Icelandic sagas, gained deeper insight into the Theory of Psychoanalysis, the theory of Self-conscious Emotions, meanings of symbols and, of course, thoroughly examined Ibsen's original texts. My research has led me to the conclusion that night dreams in The Vikings of Helgeland and Little Eyolf are of great significance for the understanding of the characters' mental, emotional and moral state and of their reasons for their actions and decisions. The use of dreams proves once more Ibsen's skills as a great writer and an expert of the human mind and psychology.